Improving Math and Science Teachers’ Understanding and Practical Skills of Case-Based Instruction: An Intensive Training Program in Bandar Lampung, Indonesia - Sunyono Sunyono; Andrian Saputra; Lisa Tania; Annisa Meristin (Bulletin of Social Studies and Community Development, 2024)
Abstract: This program was designed to bolster high school teachers' expertise in applying the case method to math and science instruction. Over six months, 19 teachers from Lampung Province participated in a structured series of lectures, workshops, and interactive sessions. The pretest and posttest evaluations highlighted significant gains in both conceptual understanding and the ability to develop case-based teaching materials. Participants were also trained to design student worksheets with digital tools like Canva, integrating scientific and socio-scientific scenarios into their lessons. By doing so, the program nurtured critical thinking, problem-solving, and environmental awareness among educators and their students. By equipping teachers with effective strategies for embedding real-world cases into their teaching, the initiative has taken a meaningful step toward advancing innovative practices in chemistry education and other scientific disciplines. To amplify its impact, expanding the program to additional regions and incorporating more classroom simulations is recommended. Such steps would further refine teachers' skills and boost student engagement with complex scientific topics. Emphasizing creativity, critical thinking, and real-world connections, this initiative represents a significant stride in enhancing high school science education. Keywords: case-based instruction, high school teachers, socioscientific issues.